Analysis of the clinical characteristics of olanzapine-induced acute pancreatitis - Yang He; Weijin Fang; Zuojun Li; Linli Sun; Yulu Zhou; Cuifang Wu; Wei Sun; Chunjiang Wang (SAGE Publishing, 2022)
Numerous case reports of acute pancreatitis (AP) induced by olanzapine have been published. Little is, however, known about the clinical features of olanzapine-induced AP. The aim of the study was to explore the clinical characteristics of olanzapine-induced AP. We collected literature on AP cases induced by olanzapine from 1996 to April 2021 for retrospective analysis in Chinese and English. The median time to onset of olanzapine-induced acute pancreatic symptoms was 12 (range = 0.86-216) weeks in 25 patients. The clinical features of AP range from asymptomatic elevation of blood amylase/lipase levels to digestive system symptoms (abdominal pain, vomiting, and nausea) and even death in a small number of patients. Laboratory tests showed varying degrees of elevated serum amylase and lipase levels, along with high blood sugar and high triglyceride levels in some patients. Computed tomography showed acute edematous pancreatitis, acute hemorrhagic pancreatitis, and acute necrotizing pancreatitis in the patients. The patients' symptoms were completely relieved and high triglyceride levels gradually returned to normal levels after olanzapine was stopped. Some patients with hyperglycemia still needed hypoglycemic therapy. AP is a rare adverse effect of olanzapine. Clinicians should be aware of such complications and monitor pancreatin.